Combined Geophysical Studies with Carried out in the Area of the Main Building of Power Project Narvani-HES on the River Narovani - Gigiberia, Malkhaz G.; Kiria, Jemal K.; Ghlonti, Nugzar Ya. (Journals of Georgian Geophysical Society, 2022)
In addition to various standard problems of Engineering Geophysics we often deal with cases that are less known in the literature, but can be quite easily solved by geophysical methods. In such cases it is important to choose an appropriate method and a convenient way to apply it. The paper describes one of such issues. The territories of the dam construction and other engineering structures connected to the river mostly cover the areas of the river gorges, which are basically presented with pebbles and rocks filling the sand. One of the most important tasks during the study of the conditions of foundation placement is to determine the bedrock depths. The pebbly rocks covering the area create great difficulties during drilling operations and geophysical surveys. In cases where the river bed is bordered by steep cliffs, both geophysical methods become difficult due to impossibility of extending communication cables to the required lengths. It is noteworthy that a part of the mentioned problems can be considered as a contributing factor for the method proposed by us in this article.